A study of relationship between stress, depression, pornography consumption among undergraduate students in Malaysia - Chua, Jing Yi (2023)
Nowadays, pornography has become very common among us, especially among young adults. This is due to the social transition and the unique features of the internet. For example, ease of access, anonymity, and so on. There are risk factors that may also contribute to increased pornography consumption even resulting in problematic pornography use or pornography addiction. This study aims to examine the relationships between stress, depression, and pornography consumption among undergraduate students in Malaysia. The cross-sectional study design and purposive sampling were conducted among 151 participants in the study. All the participants were undergraduate students in Malaysia and aged between 18 to 26 years old (M = 22.21; SD = 0.94). The number of female participants (n = 114, 75.5%) was higher than male participants (n = 37, 24.5%). The instruments used in the study were the Perceived Stress Scale (PSS-10), Patient Health Questionnaire (PHQ-9), and Pornography Usage Measure (PUM). The results and findings showed that there was no relationship between stress and pornography consumption and prediction as well. On the other hand, depression was positively correlated with and significantly predict pornography consumption. This study would provide insight for further study to explore other potential risk factors that contribute to pornography consumption among undergraduate students in Malaysia. Besides, this would also benefit professional counsellor to deal with the issue of pornography consumption among undergraduate students or young adults.